Wall panel damping device - Hejazi, Farzad; Jaafar, Mohd Saleh; Mohd Zain, Mohd Azmi (2014)
The present invention provides a viscoelastic wall panel damping device (100) that provides damping against multidirectional reacting dynamic loads that include in-plane shear force resistance and out of plane force resistance. The viscoelastic wall panel damping device (100) of the present invention, including an assembly (100a) having a pair of symmetrically opposing surfaces formed by a pair of damping element planar members (36a, 36b) that sandwiches a rigid planar member (34). The assembly (100a) being overlaid by a pair of face plates (28, 32), a proximal face plate (28) and a distal face plate (32). Aforementioned pair of face plates (28, 32) and the rigid planar member (34) of the assembly (100a) having a plurality of vertically oriented stiffener members (33) comprising of vertically oriented welded strips (33a) of steel disposed with stiffener elements (33b) at spatial intervals along the length of said welded strips of steel (33a). Aforementioned pair of face plates (28, 32) further being disposed at respective outer surfaces (28a, 32a) with a plurality of horizontal stiffener members (22).